PCR for detection of Chlamydia trachomatis in endocervical, urethral, rectal, and pharyngeal swab samples obtained from patients attending an STD clinic. Issue 6 (December 1997) - Ostergaard, L; Agner, T; Krarup, E; Johansen, U B; Weismann, K; Gutschik, E
Abstract : OBJECTIVE: To investigate, by use of the Amplicor PCR in a routine setting, the recovery rate of Chlamydia trachomatis in ano-rectal and pharyngeal swab samples obtained from males and females attending an STD clinic in relation to sexual practices, symptoms, and signs. DESIGN: Data regarding sexual practices, and symptoms and signs related to the rectum and pharynx, were obtained from 196 females and 208 males, including 31 homosexuals and eight bisexuals. Swab samples were obtained from the urethra, rectum, and pharynx from all the patients. An additional endocervical swab sample was obtained from the females. METHODS: All samples were analysed by the Amplicor PCR (Roche). SETTING: Rudolph Bergh's Hospital, a clinic for sexually transmitted diseases situated in the centre of Copenhagen, Denmark. RESULTS: The overall prevalence of urogenital C trachomatis infection was 9.2% (37/404). The specificity of the Amplicor PCR was 100% for both ano-rectal and pharyngeal swab samples. In females three (13%) of the 23 infections were detected only by testing an ano-rectal or throat swab sample. In homosexual males two (67%) of three infections were detected only by the anorectal swab sample. Ano-rectal intercourse without use of condom was reported by 44% of females and by 52% of homosexual males. Fellatio without condom use was reported by 91% of females, and 80% of heterosexual males practised cunnilingus. Pharyngeal infection, however, occurred only in females, and the presence of pharyngeal symptoms or signs seemed predictive for pharyngeal C trachomatis infection, for which the time of incubation or colonisation exceeded 3 months. The presence of ano-rectal signs or symptoms was not predictive for an ano-rectal C trachomatis infection. CONCLUSION: The Amplicor PCR can be used on ano-rectal and pharyngeal swab samples. Ano-rectal swab samples should be obtained in females and homosexual males at high risk of being infected. Pharyngeal samples should be taken in females at high risk of being infected, especially when pharyngeal signs or symptoms are present.